1999
DOI: 10.1046/j.1365-2141.1999.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

The RET receptor tyrosine kinase, but not its specific ligand, GDNF, is preferentially expressed by acute leukaemias of monocytic phenotype and is up-regulated upon differentiation

Abstract: Summary. The RET gene product represents the signaltransducing molecule of a surface receptor complex for the glial cell line-derived neurotrophic factor (GDNF), which includes GDNFR-a as a ligand-binding component. By a semi-quantitative competitive RT-PCR approach, we have analysed the relative abundances of RET transcripts in blasts purified from 40 acute myeloid leukaemia (AML) cases, revealing significant amounts of RET transcripts in 60% of AML cases (24/40). RT-PCR data was confirmed by immunocytochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Thus, genes such as PRL, C20orf103, RET, GGA2, ICSBP1, ITGA7, DAP, IRAK1, and PPARG were overexpressed almost exclusively in MYST3-CREBBP cases. Among those genes, PRL and RET have been occasionally reported to be involved in leukemogenesis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). In this regard, an increased expression of prolactin protein in blast populations has been observed in anecdotal cases of monocytic-lineage leukemia as well as in the eosinophilic cell line Eol-1 (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, genes such as PRL, C20orf103, RET, GGA2, ICSBP1, ITGA7, DAP, IRAK1, and PPARG were overexpressed almost exclusively in MYST3-CREBBP cases. Among those genes, PRL and RET have been occasionally reported to be involved in leukemogenesis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). In this regard, an increased expression of prolactin protein in blast populations has been observed in anecdotal cases of monocytic-lineage leukemia as well as in the eosinophilic cell line Eol-1 (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, STAT5A and STAT5B genes were found to be significantly underexpressed in our MYST3-CREBBP AML samples, suggesting a negative regulatory effect between prolactin and STAT5 proteins. On its turn, RET gene is a proto-oncogene that encodes a tyrosine kinase receptor expressed during normal myelomonocytic differentiation and, accordingly, has been found to be predominantly expressed in AML of monocytic phenotype (30)(31)(32). Moreover, RET mRNA levels are typically low among immature CD34 + hemopoietic progenitors whereas overexpression of this protein has been associated with coexpression of adhesion molecules such as CD56 (30).…”
Section: Discussionmentioning
confidence: 99%
“…This is a novel and interesting finding, as previous studies reported that only GDNF and GFRα1were present in two human osteosarcoma cell lines (Saos-2, MG63) and primary bone marrow stromal cells, but not RET (12). Thus this latter work had led to the conclusion that GDNF signaling in the bone marrow environment involved interaction with RET-expressing hematopoietic cells (13)(14). Previous studies have suggested that isolated cells from calvarial bones may behave differently than osteoblasts derived from long bones ((21-23)), which may reflect the mechanistically different processes by which the different structures in the skeleton develop (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…along with GDNF in bone marrow stromal cells, RET proved to be absent in these cells (12)(13). However, GDNF/GFR1 complexes cleaved from the stromal cells were shown to elicit functional signaling through RET expressed on hematopoietic and leukemic cells suggesting a signaling pathway involving cell-cell interactions within the bone marrow environment (13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation